Chinese-Based Spearcons: Improving Pedestrian Navigation Performance in Eyes-Free Environment. Issue 6 (2nd June 2016) - Hussain, Ibrar; Chen, Ling; Mirza, Hamid Turab; Wang, Liwen; Chen, Gencai; Memon, Imran
Abstract : This article presents nonspeech audio (i.e., English-based spearcons and Chinese-based spearcons) to represent distance, and forward-direction for pedestrian navigation in an eyes-free environment. Experiment in the field is carried out with the involvement of 10 participants (i.e., native Chinese) using within-subject design to evaluate English-based spearcons, Chinese-based spearcons, and Chinese text-to-speech (TTS). Results from the experiment suggest that Chinese-based spearcons are efficient in task completion compared to Chinese TTS. Moreover, Chinese-based spearcons are more effective in conveying distance and forward-direction compared to English-based spearcons in pedestrian navigation. Overall, participants have shown their satisfaction with Chinese-based spearcons as an auditory feedback in pedestrian navigation.